Paediatric Takayasu's arteritis complicated by thrombotic occlusion of the distal thoracic aorta. (3rd November 2021) - Nakata, Tomohiro; Tachi, Maiko; Suehiro, Shoichi; Oda, Teiji
Abstract: We present the case of a 1-year-old girl with mid-aortic syndrome due to untreated Takayasu's arteritis who developed cardiogenic shock. Enhanced computed tomography revealed long-segment occlusion of the distal thoracic aorta. We successfully performed graft interpose (10 mm in diameter) under cardiopulmonary bypass through both median sternotomy and left posterolateral thoracotomy. The thrombus was relatively small and the distal thoracic aorta was narrow over a long segment due to severely thickened intima. Follow-up computed tomography showed widely patent graft without a stenotic region in the abdominal aorta or its branches. The patient discharged ambulatory without major complications. Abstract : Takayasu's arteritis (TA) is an inflammatory, granulomatous and fibrosing arteritis of the aorta and its major branches [1, 2].